2019
DOI: 10.17219/dmp/109329
|View full text |Cite
|
Sign up to set email alerts
|

Management of patients with disk displacement without reduction of the temporomandibular joint by arthrocentesis alone, plus hyaluronic acid or plus platelet-rich plasma

Abstract: Background. Disk displacement without reduction (DDwoR) is one of the most common temporomandibular joint disorders (TMDs); it can manifest itself in joint pain and limited mouth opening. Nowadays, many arthrocentesis techniques are used with no consensus on which technique is optimal. Objectives. The aim of this study was to investigate the efficacy of 3 techniques in the treatment of TMD known as DDwoR and to compare them in order to determine whether one is superior to the others. Material and methods. A pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 25 publications
(35 reference statements)
2
21
0
1
Order By: Relevance
“…MMO was calculated by measuring the distance between the upper and lower central incisors, during nonforced MMO. Only 2 out of 9 studies showed significant improvement in MMO in PC group compared to HA (Hegab et al 2015) or saline (Toameh et al 2019) injections. The meta-analysis results showed nonsignificant difference between the PC group compared to HA at 3- and 12-mo follow-up, respectively [weighted mean difference (WMD), 0.97 (−0.68 to 2.63; P = 0.25), 0.23 (−3.53 to 3.99; P = 0.91) [random-effect model]].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…MMO was calculated by measuring the distance between the upper and lower central incisors, during nonforced MMO. Only 2 out of 9 studies showed significant improvement in MMO in PC group compared to HA (Hegab et al 2015) or saline (Toameh et al 2019) injections. The meta-analysis results showed nonsignificant difference between the PC group compared to HA at 3- and 12-mo follow-up, respectively [weighted mean difference (WMD), 0.97 (−0.68 to 2.63; P = 0.25), 0.23 (−3.53 to 3.99; P = 0.91) [random-effect model]].…”
Section: Resultsmentioning
confidence: 99%
“…The full text of the related studies was read by 2 researchers for potential inclusion. Of the 34 full-text studies reviewed, 9 studies met the inclusion criteria (Machon et al 2013; Comert Kilic et al 2015; Hanci et al 2015; Hegab et al 2015; Comert Kilic and Gungormus 2016; Fernandez Sanroman et al 2016; Fernandez-Ferro et al 2017; Singh et al 2019; Toameh et al 2019). The other 25 articles were excluded as they did not meet the inclusion criteria.…”
Section: Resultsmentioning
confidence: 99%
“…The standard deviation of the post-operative MMO and VAS were assumed to be the same as the pre-operative values. In 3 of the studies, arthrocentesis was performed as the initial treatment for TMDs [20][21][22][23] , in 2 of the studies, arthrocentesis was done within 3 months of failing conservative treatment 24,25 , and in 5 of the studies, arthrocentesis was performed after at least 3 months of conservative treatment [26][27][28][29][30] . Both random effects model and fixed effects models were used for construction of forest plots, due to the intention of generalization inference and the high heterogeneity found in the included studies, but also because of the small number of studies included in the meta-analysis.…”
Section: Synthesis Of Resultsmentioning
confidence: 99%
“…In 2 of the studies 24,25 , arthrocentesis was performed within 3 months of failing conservative treatment (2 weeks and 1 month). In the other 5 studies [26][27][28][29][30] , arthrocentesis…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation